The Additional Value of Endolymphatic Hydrops Imaging With Intratympanic Contrast for Diagnostic Work-Up—Experience From a Neurotology Center in Austria - Weitgasser, Lennart; O‘Sullivan, Anna; Schlattau, Alexander; Roesch, Sebastian (Frontiers in Surgery, 2021)
OBJECTIVE: To illustrate the merit of hydrops imaging during clinical workup of dizziness and balance disorders. BACKGROUND: Ever since the first description of in-vivo endolymphatic hydrops imaging in 2007, this diagnostic tool has been implemented in an increasing number of centers. As experience with its clinical application evolves, so does its ability to critically assess potential added value for diagnostic workup. This article intends to provide experience on both the handling and utilization of endolymphatic hydrops imaging in one of the first centers in Austria. METHODS: Retrospective analysis and review of clinical cases. RESULTS: Based on our experience of endolymphatic hydrops imaging (EHI), which was established in cooperation between our departments of radiology and otorhinolaryngology in 2017, we have exclusively used intratympanic application of a contrast agent prior to magnetic resonance imaging. This approach provides high quality imaging results. Since precise vestibular examination prior to EHI is necessary, it cannot replace clinical examination in the diagnostic workup but adds significantly to the interpretation of results. CONCLUSION: Endolymphatic hydrops imaging represents a valuable and well-applicable additional diagnostic tool. However, indication and evaluation of results rely on prior thorough vestibular investigations.